Habitat as an elementary operation unit of the landscape ecological mapping - Pavel V. Zhoomar (Журнал Белорусского государственного университета: География, геология, 2017)
This work is dedicated to the problem of identification of the optimal elementary operation unit of ecological mapping and its application to landscape researches. The habitat is proposed to use in the form of it. They are considered as a homogenous territory where the complex of natural conditions and its management are caused the predomination of vegetative communities, dominating species of which are relate to one or two living forms. The correspondence of terms «facies» and «habitat» is analysed and herewith the subordinate state of last has been indicated. Also the definition of general habitat category is introduced as a typological unit selected on the base of predominating living form of plants with detailed information about its environment, area, management and species composition, reflected inner structural peculiarities of facies, which have to be taken into account at their following mapping. The significance of general habitat category in the landscape science and in the landscape mapping is marked for the correlation scales composition among the actual landscape classifications. Results of the field testing of general habitat category mapping technique are adduced on the example of educational geographic station «West Berezina».